PUBLIC POLICIES TO COMBAT SEXUAL VIOLENCE AGAINST CHILDREN AND ADOLESCENTS: A STUDY OF THE CONTEXT OF RIO GRANDE DO SUL (Interdisciplinary Studies Journal, 2026)
This article aims to propose a discussion on the phenomenon of sexual violence against children and adolescents, highlighting its social impact and addressing the need for public policies aimed at prevention and response. Initially, an analysis of the scenario of sexual violence against children and adolescents is conducted, with a focus on the state of Rio Grande do Sul, including the presentation of statistical data. Subsequently, an evaluation of existing public policies in Brazil and in Rio Grande do Sul is carried out, examining their implementation within the regional context. A quantitative-qualitative exploratory-descriptive methodology is employed to investigate violence against children and adolescents in the state and to assess the effectiveness of these policies in confronting the phenomenon. Therefore, it is concluded that discussing sexual violence against children and adolescents is essential, as it involves safeguarding the rights of a vulnerable group in full development. By understanding the complexity of this phenomenon and its consequences, it becomes possible to examine existing public policies as well as the feasibility of developing more effective measures, ensuring adequate support for victims and promoting a culture of prevention and accountability.
Keywords: Public Policies; Sexual Violence Against Children and Adolescents; Rio Grande do Sul